DEVELOPMENT AND CHARACTERIZATION OF FIRE-RESISTANT CEILING BOARDS FROM LOW-DENSITY POLYETHYLENE-REINFORCED BREADFRUIT SEED COATS - Chukwulozie Okolie, Paul; Nnaemeka, Ezenwa Obiora; Princewill Odeh, Calistus; Ndubuisi Okoye, Chibuzo; Augustine Uzodinma , Madumere; Nwachinemere, Chima Bright (Universitas Ngeri Malang, 2024)
The increasing demand for sustainable composite materials has led to the exploration of agricultural waste as an alternative to wood-based particleboards. This study develops and characterizes a fire-resistant composite ceiling board using breadfruit seed coats (BSCs) reinforced with low-density polyethylene (LDPE) and kaolin. The study investigated the effects of mixture ratio, press temperature, pressure, and time on water absorption, thermal conductivity, flexural strength, and fire performance. Results showed that the lowest water absorption (2.941 percent) was achieved at 60 wt percent BSCs, 200°C, 15 MPa, and 10 min, ensuring resistance to moisture-related deterioration. The lowest thermal conductivity (0.106 Wm⁻¹K⁻¹) was recorded at 80 wt percent kaolin, 190°C, 11 MPa, and 15 min, indicating superior insulation properties. Flexural strength was highest (0.833 MPa) at 0 wt percent kaolin, while increased kaolin content significantly improved fire resistance, with a maximum Time to Ignition (224 sec) and lowest heat release rate (103 kW/m²) at 80 wt percent kaolin, 190°C, 11 MPa, and 15 min. The optimal processing conditions were 190°C, 11 MPa, and 15 min. These findings demonstrated the potential of breadfruit seed coat-based composites as fire-resistant, moisture-resistant, and thermally insulating ceiling boards, providing a sustainable alternative to conventional materials.